Preparation of high quality hematoxylin and eosin-stained sections from rodent mammary gland whole mounts for histopathologic review - Tucker, Deirdre K. (Toxicol Pathol, 2016)
Identifying environmental exposures that cause adverse mammary gland outcomes in rodents is a first step in disease prevention in humans and domestic pets. ‘Whole mounts’ are an easy and inexpensive tissue preparation method that can elucidate typical or abnormal mammary gland morphology in rodent studies. Here we propose procedures to facilitate the use of whole mounts for histological identification of grossly noted tissue alterations. We noted lesions in mammary whole mounts from 14 month old CD-1 mice that were not found in the contralateral gland hematoxylin and eosin (H&E)-stained section. Whole mounts were removed from the slide and carefully processed to produce high quality histological sections that mirrored the quality of the original H&E-stained section in order to properly diagnose the unidentified gross abnormalities. Incorporation of this method into testing protocols which focus on low-dose human relevant chemicals and endocrine disruptors will increase the chances of identifying lesions in the gland and reduce the risk of false negative findings. This method can be especially invaluable when lesions are not always palpable during the course of the study or visible at necropsy, or when a single cross-section of the mammary gland is otherwise used for detecting lesions.